Food refrigeration system using low grade energy input from renewable and sustainable sources of energy: an overview - Gupta, Anupriya; Sharma , Deepak (Journal of Postharvest Technology, 2022)
In the present era, when the rate of depletion of existing fossil fuels is increasing rapidly, it is seen that there is a global transmission towards alternate  energy sources. One such example is switching towards vapor absorption refrigeration system (VARSs) since it has many advantages than the  conventional compression refrigeration systems (VCRSs). This is because absorption refrigeration facilitates reduction of cost as it provides a very  good opportunity for using waste heat which could be from either stream or nonconventional solar, biogas, waste heat from industries, waste heat from  vehicles, geothermal energy etc. The technology does not affect the environment in any harmful way which is otherwise ill-treated by VCRSs by  depleting the protective ozone layer and the emissions of harmful greenhouse gases caused by chlorofluorocarbons used in. Also as the input fuel is  available at free or very low cost, it helps saving money. However, low COP is a point to be considered which, could be enhanced by the use of double  and triple effect VARS. In this review paper an overview of different renewable energy sources as a heat input to VARS is done.
Keywords: Refrigeration systems; food preservation; refrigerants; renewable energy source; cold storage